The Oxford handbook of classics in public policy and administration - Balla, Steven J.; Lodge, Martin; Page, Edward (Oxford University Press, 2015)
This Handbook brings together a collection of leading international authors to reflect on the influence of central contributions, or classics, that have shaped the development of the field of public policy and administration. The Handbook reflects on a wide range of key contributions to the field, selected on the basis of their international and wider disciplinary impact. Focusing on classics that contributed significantly to the field over the second half of the 20th century, it offers insights into works that have explored aspects of the policy process, of particular features of bureaucracy, and of administrative and policy reforms. Each classic is discussed by a leading international scholars. They offer unique insights into the ways in which individual classics have been received in scholarly debates and disciplines, how classics have shaped evolving research agendas, and how the individual classics continue to shape contemporary scholarly debates. In doing so, this volume offers a novel approach towards considering the various central contributions to the field. The Handbook offers students of public policy and administration state-of-the-art insights into the enduring impact of key contributions to the field
Keywords: Aufsatzsammlung; Verwaltungshandeln; Verwaltung; Staatstätigkeit; Verwaltungslehre